Learning Models Through Cybergogy in the Digital Era - Anas Rohman; Rusdarti Rusdarti; Kardoyo Kardoyo; Sungkowo Edy Mulyono (Universitas Negeri Semarang, 2023)
this article aim study neighbour development of online learning models in the digital era. In study This discussed neighbour cybergogy as a learning model online research _ about the influencing factors child educate in online learning , namely cognitive , emotional and social factors . So that these three factors can made as attention main a educator in do online learning in order three factor can controlled , which thing This impact to achievements cognitive , emotional and social child educate in learn . Therefore , the cybergogy model education requires a problem - based strategy social , because of this strategy can integrated with harmonious with three factors cybergogy , so can form cognitive , emotional and sensitivity social child educate .